2022
DOI: 10.34133/2022/9843093
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ca Alloy Composite Anode with Ant-Nest-Like Lithiophilic Channels in Carbon Cloth Enabling High-Performance Li Metal Batteries

Abstract: Constructing a three-dimensional (3D) multifunctional hosting architecture and subsequent thermal infusion of molten Li to produce advanced Li composite is an effective strategy for stable Li metal anode. However, the pure liquid Li is difficult to spread across the surface of various substrates due to its large surface tension and poor wettability, hindering the production and application of Li composite anode. Herein, heteroatomic Ca is doped into molten Li to generate Li-Ca alloy, which greatly regulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…It is crucial to have a Li-metal alloy that is less expensive, exhibits less volume expansion, has sufficient theoretical capacity, and has improved Li kinetics. Ca metal is the fifth most abundant element on Earth’s crust and has a substantial global distribution. , The Li–Ca alloy is less expensive, has superior Li-ion kinetics, and is less overpotential. Due to these characteristics of the Li–Ca system, we modified the interface between the Li anode and SE using the Li–Ca alloy. Further, the Li–Ca alloy is used in liquid electrolyte-based lithium-ion batteries to stabilize the lithium-metal interface; however, it has not yet been employed in solid-state electrolyte-based lithium-ion batteries. Therefore, to improve the performance of all-solid-state cell with the LSiPS solid electrolyte, the Li/LSiPS interface was further modified by adding a minimum amount of the synthesized liquid electrolyte using the concept of the lithiophilic–lithiophobic interface construction.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to have a Li-metal alloy that is less expensive, exhibits less volume expansion, has sufficient theoretical capacity, and has improved Li kinetics. Ca metal is the fifth most abundant element on Earth’s crust and has a substantial global distribution. , The Li–Ca alloy is less expensive, has superior Li-ion kinetics, and is less overpotential. Due to these characteristics of the Li–Ca system, we modified the interface between the Li anode and SE using the Li–Ca alloy. Further, the Li–Ca alloy is used in liquid electrolyte-based lithium-ion batteries to stabilize the lithium-metal interface; however, it has not yet been employed in solid-state electrolyte-based lithium-ion batteries. Therefore, to improve the performance of all-solid-state cell with the LSiPS solid electrolyte, the Li/LSiPS interface was further modified by adding a minimum amount of the synthesized liquid electrolyte using the concept of the lithiophilic–lithiophobic interface construction.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] As the holy grail of anode materials, lithium metal has become a research hotspot for next-generation lithium metal batteries (LMBs) because of its low reduction potential (−3.04 V versus standard hydrogen electrode) and high theoretical specific capacity (3860 mAh g −1 ) which is ten times that of graphite. [5][6][7] However, excess lithium not only increases the DOI: 10.1002/aenm.202303918 manufacturing cost, but also reduces the volumetric energy density, which is unfriendly to power batteries. [8] At this point, anode-free lithium metal batteries (AFLMBs) are the most promising nextgeneration LMBs since they directly employ copper foil as the anode to maximize the volumetric energy density of the battery and reduce manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…The NMR approach is regarded as a powerful method for in situ detection of dead lithium due to its non-invasive inherent features. Recently, Brunklaus et al reported a scheme to quantify irreversible lithium loss in batteries using in situ and ex situ 7 Li solid-state NMR spectroscopy, clearly distinguishing the capacity loss due to SEI and dead lithium, respectively. [24] Subsequently, Grey and coworkers utilized in situ 7 Li solid-state NMR to track the formation of dead lithium in AFLMBs and further investigated the rate of corrosion of lithium metal during the open circuit.…”
Section: Introductionmentioning
confidence: 99%
“…A Li-rich Li-Ca alloy composited with carbon cloth provides a secondary network composed of the CaLi 2 intermetallic compound with interconnected ant-nest-like lithiophilic channels across the primary scaffold of the carbon cloth matrix and exhibits a long-term lifespan. 49 Hence, a hybrid of a carbon cloth sheet with a lithiophilic Li-rich alloy fabricated by a facile way might be a promising candidate to prolong the lifespan of the Li metal anode.…”
Section: Introductionmentioning
confidence: 99%